INVESTIGATING JUNIOR HIGH SCHOOL STUDENTS' CRITICAL THINKING IN READING - Putri, Okti (2014)
This study is concerned with investigating the third year students' Critical Thinking (CT) in reading in a junior high school in Bandung. This study employed a qualitative case study. The data were obtained through reading tests and classroom observations. The data were analyzed based on the theory of CT in reading as developed by Ennis (1996), Chaffee (2000), Fisher (2001), Wallace (2003), Emilia (2005), Bassham et al. (2008), and Paul & Elder (2008). This includes CT components, CT standards, CT skills and abilities, and CT dispositions applied in reading. The results of the study reveal that the students had already applied their CT ability in reading. It can be seen from the results of their reading tests and classroom observations. The findings show that there are some aspects of CT in reading that had been demonstrated in students' reading tests and activities. Regarding CT components, the students were able to identify topic, main idea and argument. In the case of skills and abilities of critical reading, the students had good ability in making personal response, drawing conclusion/making inference, and evaluating on how the writer organizes the text. Moreover, the students also have already demonstrated some aspects of CT in the reading activities such as identifying topic and main idea, drawing conclusion, predicting the text, and paraphrasing. Regarding the CT dispositions, the students were well-informed, creative questioners, and open-minded. However, the reading tests and observations also show the students' weaknesses regarding the standards, skills and abilities of CT in reading. In CT standards, the students were not able to answer the questions in the case of clarity, accuracy, precision, logic and relevance. With regards to skills and abilities of critical reading, the students faced difficulties in analyzing the author's position and reading between the lines. The students' ability in critical reading still needs improvement and guidance from the teacher. It can be seen from the difficulties faced by the students in answering questions that need critical reading ability. The findings suggest that the teacher should guide the students in reading critically. It is important for the teacher to provide activities that promote CT in reading.